1996
DOI: 10.1111/j.1439-0388.1996.tb00631.x
|View full text |Cite
|
Sign up to set email alerts
|

Liposome‐mediated gene transfer via sperm cells. High transfer efficiency and persistence of transgenes by use of liposomes and sperm cells and a murine amplification element

Abstract: Summary Plasmid DNA was encapsulated in liposomes to protect from degradation and to support the incorporation into sperm cells. Transgenic spermatozoa carry the foreign DNA to the target cell when fertilizing the egg. Several plasmid constructs were transferred into rabbits, cattle and chicken. The plasmid apparently can persist when provided with a murine amplification promoting sequence. The transgeneity of sperm cells as well as fetuses or offspring was demonstrated by dot blot, Southern blot analysis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…For example, Bachillar et al [32] reported that liposome-encapsulated foreign DNA can be incorporated into mouse sperm head after culture with spermatozoa isolated from the epididymis, though transgenic animals could not be generated by the sperm. However, the property of transporting exogenous DNA into the oocyte via sperm has been recently described in several species [12][13][14][15][16][17][18]. Together with the present data, these results indicate that sperm cells can be used as a vector transferring the gene under certain experimental condition.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…For example, Bachillar et al [32] reported that liposome-encapsulated foreign DNA can be incorporated into mouse sperm head after culture with spermatozoa isolated from the epididymis, though transgenic animals could not be generated by the sperm. However, the property of transporting exogenous DNA into the oocyte via sperm has been recently described in several species [12][13][14][15][16][17][18]. Together with the present data, these results indicate that sperm cells can be used as a vector transferring the gene under certain experimental condition.…”
Section: Discussionsupporting
confidence: 72%
“…By this conventional microinjection method, we have already produced 2 lines of transgenic rats expressing human growth hormone (hGH) gene under the control of mouse whey acidic protein (WAP) promoter [4][5][6]. However, it requires spe- [9][10][11], successful sperm-mediated gene transfer has been now reported in a variety of animal species including mollusk [12], insect [13], fish [14], bird [15] and mammals [16][17][18]. It would be a more useful alternative, especially on laboratory animals such as rats and mice, if an injection of DNA into the testis could generate transgenic animals via sperm ejaculated (testis-mediated gene transfer).…”
mentioning
confidence: 99%
“…One of the more convenient alternatives is sperm-mediated gene transfer (SMGT), which uses spermatozoa as vectors for DNA delivery [5]. A large number of transgenic animals including mice, pigs and cattle have been produced by SMGT using sperm associated with naked DNA or liposome-DNA complex [6][7][8][9][10][11][12]. However, the efficiency and reliability of SMGT are still controversial [13,14], though the capacity of spermatozoa capturing foreign DNA has been proven [15,16].…”
mentioning
confidence: 99%
“…Since the pioneering study by Brackett et al [1] showing that rabbit spermatozoa were able to incorporate SV40 DNA into their heads during incubation, the property of association of spermatozoa with heterologous DNA has been extensively studied [2][3][4][5]. These studies have facilitated the idea of using sperm as a vector to transfer exoge-actually carry the DNA into eggs, and the gene thus transferred is transcriptionally active [11][12][13][14][15][16][17]. In addition, as described in the associated paper [18], we have shown that DNAs injected into the testis of either rats or mice can be transferred into eggs via sperm at fertilization (testis-mediated gene transfer).…”
mentioning
confidence: 99%